Covid-19 and Pregnancy: Clinical Case of Critical Presentation, Placental Inflammation and Demonstrated Fetal Vertical Transmission [Covid-19 y Embarazo: Caso Clínico de Presentación Crítica, Inflamación Placentaria y Transmisión Vertical Fetal Demostrada] - Haye-Morales, M (Ediciones Doyma, S.L., 2021)
Background: The global COVID-19 pandemic reaches the American continent in March 2020 and in less than two months it brings together more than half of the cases globally. Objective: The clinical case of a 25-week pregnant woman with a critical presentation of COVID-19 and pregnancy at 25 weeks of gestation, is presented in the context of the peak of the pandemic in Chile in the fall of 2020. Clinical case: On June 20, 2020, a 34-year-old woman, 25 weeks pregnant, is transferred from Hospital de San Bernardo to Clinica Las Condes in Santiago, Chile, with a ten-day evolution of a COVID-19 that evolves to critical with severe respiratory failure. She is admitted to the intensive care unit for mechanical ventilation. Chest computerized axial tomography images demonstrate bilateral pneumopathy with characteristic images of ground-glass opacities, associated with interstitial thickening, images previously described as characteristics for COVID-19. The patient remains in the intensive care unit on mechanical ventilation for seven days, with subsequent favorable evolution, improvement of the septic condition, and discharge after 22 days of hospitalization. Delivery occurs at 38 weeks, the mother and the newborn evolve in good general condition. The placental histopathological examination demonstrates villous inflammatory involvement, and the newborn s blood tests show the presence of IgG and IgM antibodies. It is one of the few reported cases of transplacental transmission of SARS-CoV-2 from the mother to the newborn. © 2021